2011
DOI: 10.1063/1.3623272
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of spherical gas interfaces accelerated by a planar shock wave

Abstract: The interaction of a planar shock wave with a spherical gas interface (SF6 or helium) surrounded by air is studied experimentally and numerically. By means of the high-speed schlieren photography with high time resolutions and the numerical method VAS2D, the detailed flow field structures including the evolution of interfaces and the development of wave patterns are obtained. The sequences of schlieren frames of SF6 show that the refracted shock wave converges inside the volume and causes the shock focusing wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 27 publications
2
43
0
7
Order By: Relevance
“…The development of shock-accelerated polygonal interfaces, illuminated by a DC regulated light source (DCR III, SCHOTT North America, Inc.), is captured by high-speed schlieren photography as presented in figure 2. In order to facilitate the light passing through the test section vertically, two parallel planar mirrors with a diameter of 200 mm are added in the traditional Z-fold schlieren system (Zhai et al 2011;Si et al 2012). In the present study, the frame rate of the high-speed video …”
Section: Experimental and Numerical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of shock-accelerated polygonal interfaces, illuminated by a DC regulated light source (DCR III, SCHOTT North America, Inc.), is captured by high-speed schlieren photography as presented in figure 2. In order to facilitate the light passing through the test section vertically, two parallel planar mirrors with a diameter of 200 mm are added in the traditional Z-fold schlieren system (Zhai et al 2011;Si et al 2012). In the present study, the frame rate of the high-speed video …”
Section: Experimental and Numerical Methodsmentioning
confidence: 99%
“…The shapes of the gas interface in previous studies mainly include the single-mode interface (Meshkov 1969;Brouillette 2002;Jacobs & Krivets 2005;Mariani et al 2008;Long et al 2009;Balakumar et al 2012;, the spherical or cylindrical bubble formed by a soap film (Haas & Sturtevant 1987;Hosseini & Takayama 2005;Layes, Jourdan & Houas 2009;Haehn et al 2011Haehn et al , 2012Zhai et al 2011;Si et al 2012), the membrane-less gas cylinder (Jacobs 1992(Jacobs , 1993Tomkins et al 2008;Zhai et al 2014;Zou et al 2010) or gas curtain Orlicz et al 2009;Balakumar et al 2012;Balasubramanian et al 2012;Tomkins et al 2013) formed by the jet technique and the inclined planar interface (Wang et al 2012;McFarland et al 2014). Besides these classical interface shapes, Mikaelian (2005) theoretically and numerically studied the RMI on an initial interface with a discontinuous change in its first derivative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of a planar shock, different techniques developed to form the initial interfaces have been reported in the literature. Typically, the interfaces of different shapes between two gases include spherical bubbles formed by a soap film (Haas & Sturtevant 1987;Layes, Jourdan & Houas 2003;Ranjan et al 2005;Zhai et al 2011;Si et al 2012), circular gas cylinders (Haas & Sturtevant 1987;Hosseini & Takayama 2005;Tomkins et al 2008;Luo et al 2014b), elliptical gas cylinders On converging shock and polygonal interface interaction 227 (Zou et al 2010), single-/multi-mode interfaces generated by vibration (Jacobs & Sheeley 1995;Mariani et al 2008;Long et al 2009) or by a gas curtain (Balakumar et al 2008;Orlicz et al 2009;Balasubramanian et al 2012), rectangular blocks generated by a microfilm membrane supported by a fine wire mesh (Bates, Nikiforakis & Holder 2007), and three-dimensional interfaces with a minimum surface feature formed by the soap film technique free of supporting meshes . Recently, some polygonal interfaces have been formed in our group using thin pins to restrict the soap film and the results indicate that the soap film is a flimsy but durable material during the interface formation Zhai et al 2014;Luo et al 2015).…”
mentioning
confidence: 99%
“…Considerable work was also performed by domestic researchers, such as Li et al [21], Bai et al [22], and Tian et al [23]. Recent work by Zhai et al [24] emphasized the complex process involved during the shock focusing experimentally and computationally on the converging bubble scenario. It can be found that previous studies mainly concentrate on the development of initial perturbation and subsequently the occurrence of turbulent mixing after the shock wave passage.…”
Section: Introductionmentioning
confidence: 96%